Production of Bioplastic by Polyhydroxybutyrate (PHB) accumulating Bacillus megaterium VAS05 and Determination of its Chemical and Mechanical Characteristics (International Journal of Food and Nutritional Sciences, 2022)
The Polyhydroxybutyrate (PHB) producing Bacillus megaterium was isolated from organic waste dumping sites in Kannur, Thalassery, Kannur District, Kerala, India. The strain identity was confirmed through biochemical tests and molecular sequencing and was designated Bacillus megaterium VAS05; the nucleotide sequence was submitted in GenBank with accession no. MW193404. The PHB production maximized at an incubation period of 72 h (4.1 g/l); the optimum PHB production was noted at a temperature 37°C and pH 7.0 in which 63.71 % and 62.13% yield respectively of the biopolymer was obtained. The supplementation of the carbon sources (1% w/v), sucrose and lactose separately with the Minimal Davis medium yielded high level of PHB (5.44 and 5.57 g/l respectively). The nitrogen sources studied couldn’t impact the production of PHB (ammonium sulphate, beef extract, malt extract) except for Green Gram powder (1% w/v), the supplementation of which as the sole source of nitrogen yielded 6.04 g/l of PHB. The PHB was partially purified by hot chloroform precipitation and bioplastic sheet was prepared. The FTIR analysis showed the characteristic peaks corresponding to C─H, C═O, OH functional groups and strong stretching peaks within the range of 1800 and 1600 cm-1. The XRD analysis revealed intense peak at 31.83˚ indicating crystalline nature of PHB. The thermal transition of the bioplastic was noted at a temperature of 106.07°C. The tensile strength of the extracted bioplastic film was very low (1.38 MPa) which necessitates further experiments towards improving the mechanical properties of the bioplastic. Evident degradation could be observed for biopolymer after 40 days of burial in the soil while the synthetic plastic sheet remained unaltered. The study revealed the possible prospects of bioplastic from PHB produced by soil bacteria as a better alternative to the synthetic non-degradable plastics.